2014
DOI: 10.1111/jmp.12124
|View full text |Cite
|
Sign up to set email alerts
|

SHIV susceptibility changes during the menstrual cycle of pigtail macaques

Abstract: Background Hormonal changes during menstrual cycling may affect susceptibility to HIV. Methods We determined the SHIV acquisition time point in 43 cycling pigtail macaques infected by repeated vaginal virus exposures initiated randomly in the cycle. Results SHIV infection was first detected in the follicular phase in 38 macaques (88%), and in the luteal phase in 5 macaques (12%), indicating a statistically significant timing difference. Assuming a 7-day eclipse phase, most infections occurred during or fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 15 publications
3
74
0
Order By: Relevance
“…14 No difference in vaginal tissue gene expression (greater than twofold) between FOL and LUT phases Using microarray, we found that gene expression in vaginal tissue was not significantly dysregulated by more than twofold in the FOL phase versus the LUT phase of the menstrual cycle. Only one gene, HAL, was significantly upregulated (2.4-fold) in the LUT phase compared with the FOL phase.…”
Section: No Differences In Vaginal Ph or Nugent Score Between Fol Andmentioning
confidence: 73%
See 2 more Smart Citations
“…14 No difference in vaginal tissue gene expression (greater than twofold) between FOL and LUT phases Using microarray, we found that gene expression in vaginal tissue was not significantly dysregulated by more than twofold in the FOL phase versus the LUT phase of the menstrual cycle. Only one gene, HAL, was significantly upregulated (2.4-fold) in the LUT phase compared with the FOL phase.…”
Section: No Differences In Vaginal Ph or Nugent Score Between Fol Andmentioning
confidence: 73%
“…Studies demonstrated that rhesus 12 and pigtail macaques 13,14 were more vulnerable to Simian human immunodeficiency virus (SHIV) infection in the LUT phase of the menstrual cycle 13 and this vulnerability to infection persisted during menstruation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hormonal fluctuations during normal menstrual cycle cause changes in mucosal immunity that may predispose to genital viral infections. Increased susceptibility to infection with human immunodeficiency virus (HIV) or simian HIV (SHIV) was noted to occur during the time after ovulation corresponding to the diestrus stage of the reproductive cycle in rodents (21,22). The injectable medroxyprogesterone acetate formulation DepoProvera (DMPA) modulates menstrual cycle in humans and was shown to induce diestrus and to predispose small animals to more severe HSV-2 infection (23).…”
Section: Resultsmentioning
confidence: 99%
“…It has been hypothesized that such cycledependent changes in immune responses engender variable susceptibilities to sexually transmitted infections (STIs), including HIV-1. We have previously demonstrated using a repeat, lowdose virus challenge model that there are various susceptibilities to simian-human immunodeficiency virus (SHIV) during the different menstrual phases in female pig-tailed macaques (Macaca nemestrina) (6,7). With menstrual cycling patterns similar to those in humans, and the previously reported success in infecting the animals at low virus doses without hormonal intervention, pig-tailed macaques have become unique animal models for HIV studies; their importance is especially underscored in testing menstrual phase-dependent susceptibility to HIV, considering the difficulty in conducting such studies with normally cycling women.…”
mentioning
confidence: 99%